Ipsilesional versus contralesional postural deficits induced by unilateral brain trauma: a side reversal by opioid mechanism. Issue 2 (13th December 2020) - Watanabe, Hiroyuki; Nosova, Olga; Sarkisyan, Daniil; Andersen, Marlene Storm; Zhang, Mengliang; Rorick-Kehn, Linda; Clausen, Fredrik; Gawel, Kinga; Kehr, Jan; Hallberg, Mathias; Schouenborg, Jens; Marklund, Niklas; et al.
Abstract: Unilateral traumatic brain injury and stroke result in asymmetric postural and motor deficits including contralateral hemiplegia and hemiparesis. In animals, a localized unilateral brain injury recapitulates the human upper motor neuron syndrome in the formation of hindlimb postural asymmetry with contralesional limb flexion and the asymmetry of hindlimb nociceptive withdrawal reflexes. The current view is that these effects are developed due to aberrant activity of motor pathways that descend from the brain into the spinal cord. These pathways and their target spinal circuits may be regulated by local neurohormonal systems that may also mediate effects of brain injury. Here, we evaluate if a unilateral traumatic brain injury induces hindlimb postural asymmetry, a model of postural deficits, and if this asymmetry is spinally encoded and mediated by the endogenous opioid system in rats. A unilateral right-sided controlled cortical impact, a model of clinical focal traumatic brain injury was centred over the sensorimotor cortex and was observed to induce hindlimb postural asymmetry with contralateral limb flexion. The asymmetry persisted after complete spinal cord transection, implicating local neurocircuitry in the development of the deficits. Administration of the general opioid antagonist naloxone and μ-antagonist β-funaltrexamine blocked the formation of postural asymmetry. Surprisingly, κ-antagonists nor-binaltorphimine and LY2444296 did not affect the asymmetry magnitude but reversed the flexion side; instead of contralesional (left) hindlimb flexion the ipsilesional (right) limb was flexed. The postural effects of the right-side cortical injury were mimicked in animals with intact brain via intrathecal administration of the opioid κ-agonist (2)-(trans)-3, 4-Dichloro-N-methyl-N-[2-(1-pyrrolidiny)-cyclohexyl]benzeneacetamide that induced hindlimb postural asymmetry with left limb flexion. The δ-antagonist naltrindole produced no effect on the contralesional (left) flexion but inhibited the formation of the ipsilesional (right) limb flexion in brain-injured rats that were treated with κ-antagonist. The effects of the antagonists were evident before and after spinal cord transection. We concluded that the focal traumatic brain injury-induced postural asymmetry was encoded at the spinal level, and was blocked or its side was reversed by administration of opioid antagonists. The findings suggest that the balance in activity of the mirror symmetric spinal neural circuits regulating contraction of the left and right hindlimb muscles is controlled by different subtypes of opioid receptors; and that this equilibrium is impaired after unilateral brain trauma through side-specific opioid mechanism. Abstract : It was demonstrated that the mirror symmetric spinal neurocircuits regulating the left and right hindlimb muscles may be differentially controlled by opioid receptor subtypes, and that selective opioid antagonists may restore the balance in the left–right hindlimb regulation impaired after unilateral traumatic brain injury or reverse the side of affected limb. Graphical Abstract: